Graphene coated silica microfiber for highly sensitive magnesium sensor - Yasin, Moh; Irawati, Ninik; Isa, Naimah Mat; Harun, Sulaiman Wadi; Ahmad, Fauzan (Elsevier, 2018)
A high sensitivity and simple magnesium sensor based on an silica optical microfiber coated with graphene for the detection of different concentrations of magnesium in de-ionized water is developed and demonstrated. The silica microfiber probe is fabricated by flame brushing technique and it has a waist diameter of 6 μm with tapering length of 3 cm. The microfiber is coated with graphene, which functions as a sensing layer using drop coating method. It is observed that the output power from the probe decreases as the magnesium concentration increases. Without the graphene coating, the sensor has a sensitivity of 12.1 dB/% with slope linearity of more than 98.31% and resolution of 0.0102%. However, the sensitivity of the sensor is significantly improved to 19.63 dBm/% with better slope linearity of 99.25% and resolution of 0.0038% as the graphene is coated onto the silica microfiber probe. The resonant peak also shifts to a longer wavelength as the concentration of magnesium solution increased.